PENGARUH KARAKTERISTIK KOMITE AUDIT TERHADAP PENGUNGKAPAN ETIKA SUKARELA DAN IMPLIKASI TERHADAP HARGA SAHAM - Herry Laksito (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2020)
The objectives of this paper is to investigate the impact of audit committee characteristics on voluntary ethics disclosure and its implications on stock price.  Independent variable in this paper is measured using four elements of audit committee characteristics consist of competency, the number of meeting, scope, tenure and multiple directorships.  On the other hand this paper uses the stock price as dependent variable and voluntary ethical disclosure as mediating variable. The population in this paper are all companies listed on the Indonesian Stock Exchange in 2018. Sample selection method using purposive sampling and the number of samples attained as many as 94 companies. This analysis used in this paper is a multiple regression analysis. The results of this study show that the number of meeting and multiple directorship were significantly associated with the voluntary ethics disclosure, while competency, size and tenure were not significantly associated with the voluntary ethics disclosure. The study also found  a positive and significant effect between voluntary ethical disclosure and company stock prices.